MULTIMEDIA PEMBELAJARAN BERBASIS KOMPUTER SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA - Laila Nursafitri (LPPM STAI DARUSSALAM LAMPUNG, 2013)
Development of science and technology in all fields exert influence either directly or indirectly, to the quality of the teaching learning to be achieved, therefore, efforts should be done to improve the quality of learning in the case which has remained low. Generally poor quality of learning can be seen from both sides which is from the side and from the side of the result. Multimedia learning is a component that can be used in supporting the learning process. It is firmly based on the perception that learning will take place with good, effective, and fun if supported by a learning medium to attract interest and attention of students. Using computer-based multimedia can make students better remember the material being learned. Therefore highly effective multimedia and become a powerful tool in teaching and education. The use of multimedia software in teaching and learning process will increase efficiency, enhance motivation, facilitating active learning, facilitate the experimental study, consistent with the study based on the student, and the drive to learn better.